Prehospital Noninvasive Ventilation for Acute Respiratory Failure: Systematic Review, Network Meta‐analysis, and Individual Patient Data Meta‐analysis. (September 2014) - Goodacre, Steve; Stevens, John W.; Pandor, Abdullah; Poku, Edith; Ren, Shijie; Cantrell, Anna; Bounes, Vincent; Mas, Arantxa; Payen, Didier; Petrie, David; Roessler, Markus Soeren; Weitz, Gunther; et al.
Abstract Objectives This meta‐analysis aimed to determine the effectiveness of prehospital continuous positive airway pressure (CPAP) or bilevel inspiratory positive airway pressure (BiPAP) in acute respiratory failure. Methods Fourteen electronic databases and research registers were searched from inception to August 2013. Randomized or quasi‐randomized controlled trials that reported mortality or intubation rate for prehospital CPAP or BiPAP were selected and compared to a relevant comparator in patients with acute respiratory failure. An aggregate data network meta‐analysis was used to jointly estimate intervention effects relative to standard care. A network meta‐analysis using a mixture of individual patient‐level data and aggregate data was carried out to assess potential treatment effect modifiers. Results Eight randomized and two quasi‐randomized controlled trials (six CPAP, four BiPAP, sample sizes 23 to 207) were identified. The aggregate data network meta‐analysis suggested that CPAP was the most effective treatment in terms of mortality (probability = 0.989) and intubation rate (probability = 0.639) and reduced both mortality (odds ratio [OR] = 0.41; 95% credible interval [CrI] = 0.20 to 0.77) and intubation rate (OR = 0.32; 95% CrI = 0.17 to 0.62), compared to standard care. The effect of BiPAP on mortality (OR = 1.94; 95% CrI = 0.65 to 6.14) and intubation rate (OR = 0.40; 95% CrI = 0.14 to 1.16) was uncertain. The network meta‐analysis using individual patient‐level data and aggregate data suggested that sex was a modifier of the effect of treatment on mortality. Conclusions Prehospital CPAP can reduce mortality and intubation rates compared to standard care, while the effectiveness of prehospital BiPAP is uncertain.